Cadmium biosorption and mechanism investigation using a novel Bacillus subtilis KC6 isolated from pyrite mine. (20th August 2021) - Xie, Yanluo; He, Nan; Wei, Mingyang; Wen, Tingyao; Wang, Xitong; Liu, Huakang; Zhong, Shiqiang; Xu, Heng
Abstract: Cadmium (Cd)-remediation by microorganisms has been frequently used due to environmental friendliness, low cost and easy operation. However, the mechanisms of bio-remediation were not clear enough. Hence, a strain KC6, identified as Bacillus subtilis, was isolated from the metal contaminated soil around an open-air pyrite mine. KC6 had high resistance to Cd (about 100 mg L −1 ) and was able to produce siderophores (0.66 A/Ar) and solubilize phosphate (21.98 mg L −1 ). Besides, in the optimum experiment, Bacillus subtilis KC6 showed the greatest ability to remove Cd with pH 7 and 35 °C, and the revolution had little effect on Bacillus subtilis KC6 adsorbing Cd. Moreover, Bacillus subtilis KC6 had higher Cd sorption ability under 10 and 40 mg/L Cd treatment about 86.33%, 65.33%, respectively. Through Scanning Electron Microscope - Energy Dispersive Spectrometer (SEM-EDS), Fourier transform infrared spectra (FTIR) and element mapping analyses, Cd in solution was bonded onto cell walls of KC6 by increasing functional groups. Besides, under Cd stress, low molecular weight organic acids (malic acid, oxalic acid, citric acid and succinic acid) produced by strain KC6 increased significantly compared to non-Cd treatment. The various functional groups and exudates could help KC6 to chelate Cd to Cd-ligands complexes so that Cd could be bonded onto cell wall and transport into cellular organs and cytoplasm. Graphical abstract: Image 1 Highlights: Bacillus subtilis KC6 is from the contaminated soil and used for soil remediation. Cadmium reduction of Bacillus subtilis KC6 could achieve 86.33%. The mechanism of Cd removal by Bacillus subtilis KC6.